Adaptation of several types of upland rice to aluminum stress and blast disease on Ultisols in Lampung Province - Priyadi, Priyadi; Taisa, Rianida; Dulbari, Dulbari; Rochman, Fajar; Rahmadi, Rizky (Universitas Muhammadiyah Mataram, 2023)
Ultisol soil has a high aluminum content and is often attacked by blast disease, which inhibits the growth and production of upland rice plants. This study aims to obtain varieties and lines of upland rice tolerant to aluminum stress and blast disease planted on Ultisol Lampung. The study used a randomized complete block design (RCBD) with 8 types of lines and 4 varieties; The experiment was repeated three times. The results showed that line 2 (PL47)-7 was better than the other lines as indicated by productive tillers of 16.8 stems, flowering age of 50% (72.12 days), number of filled grains per panicle of 75.56 grains, the weight of 100 grains of 2.70 g, yield per harvest plot of 172.51 g/ 10 m2, Aluminum stress has a score of 3 with normal growth indicators, but there are white or yellow spots on the tips of old leaves (20–39%), and neck blast has no symptoms with a score of 0.